Efficacy and safety of percutaneous microwave coagulation therapy followed by 125I seed brachytherapy for VX2 hepatic tumors in a rabbit model - Yu, Dong-Sheng; Sommer, Christof-Matthias (Experimental and Therapeutic Medicine, 2013)
The aim of this study was to evaluate the efficacy and safety of percutaneous microwave coagulation therapy (PMCT) followed by 125I seed brachytherapy for VX2 liver cancer in rabbits. Eighty New Zealand rabbits were injected with suspensions of VX2 tumor cells to create an animal model. The rabbits were randomly divided into 4 groups (n=20); the control, PMCT, 125I seed brachytherapy and combination groups. Group A was treated with PMCT at 40 W for 120 sec, group B was treated with 125I seed brachytherapy and group C was treated with PMCT followed by 125I seed brachytherapy. Group D were not treated and served as the control group. At 21 days after treatment, the rabbits were sacrificed for pathological assessment. The complete tumor necrosis rate was 19 out of 20 tumors (95%) in group C, 6 (30%) in group A, 0 (0%) in group B and 0 (0%) in the control group. The complete tumor necrosis rate was observed to be significantly different between groups C and A, and between groups C and B (P<0.01). No intraheptic metastasis occurred in group C, compared with an incidence of 7 (35%) in group A, 2 (10%) in group B and 20 (100%) in the control group. Between groups C and A, and between groups C and D, the intraheptic metastasis rate was statistically significant (P<0.01). PMCT followed by 125I seed brachytherapy increased the rate of carcinoma necrosis and decreased carcinoma metastasis in the VX2 rabbit model. This combined treatment is a safe, effective and minimally invasive therapeutic option for liver cancer.
Gesehen am 26.07.2021